Infection of Porcine Circovirus 2 (PCV2) in Intestinal Porcine Epithelial Cell Line (IPEC-J2) and Interaction between PCV2 and IPEC-J2 Microfilaments - Yan, Mengfei (Virol J, 2014)
BACKGROUND: Porcine circovirus-associated disease (PCVAD) is caused by a small pathogenic DNA virus, Porcine circovirus type 2 (PCV2), and is responsible for severe economic losses. PCV2-associated enteritis appears to be a distinct clinical manifestation of PCV2. Most studies of swine enteritis have been performed in animal infection models, but none have been conducted in vitro using cell lines of porcine intestinal origin. An in vitro system would be particularly useful for investigating microfilaments, which are likely to be involved in every stage of the viral lifecycle. METHODS: We confirmed that PCV2 infects the intestinal porcine epithelial cell line IPEC-J2 by means of indirect immunofluorescence, transmission electron microscopy, flow cytometry and qRT-PCR. PCV2 influence on microfilaments in IPEC-J2 cells was detected by fluorescence microscopy and flow cytometry. We used Cytochalasin D or Cucurbitacin E to reorganize microfilaments, and observed changes in PCV2 invasion, replication and release in IPEC-J2 cells by qRT-PCR. RESULTS: PCV2 infection changes the ultrastructure of IPEC-J2 cells. PCV2 copy number in IPEC-J2 cells shows a rising trend as infection proceeds. Microfilaments are polymerized at 1 h p.i., but densely packed actin stress fibres are disrupted and total F-actin increases at 24, 48 and 72 h p.i. After Cytochalasin D treatment, invasion of PCV2 is suppressed, while invasion is facilitated by Cucurbitacin E. The microfilament drugs have opposite effects on viral release. CONCLUSION: PCV2 infects and proliferates in IPEC-J2 cells, demonstrating that IPEC-J2 cells can serve as a cell intestinal infection model for PCV2 pathogenesis. Furthermore, PCV2 rearranges IPEC-J2 microfilaments and increases the quantity of F-actin. Actin polymerization may facilitate the invasion of PCV2 in IPEC-J2 cells and the dissolution of cortical actin may promote PCV2 egress.